2021
DOI: 10.1007/s00380-020-01755-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole-body neuromuscular electrical stimulation device on hemodynamics, arrhythmia, and sublingual microcirculation

Abstract: Neuromuscular electrical stimulation has been used to treat cardiovascular diseases and other types of muscular dysfunction. A novel whole-body neuromuscular electrical stimulation (WB-NMES) wearable device may be beneficial when combined with voluntary exercises. This study aimed to investigate the safety and effects of the WB-NMES on hemodynamics, arrhythmia, and sublingual microcirculation. The study included 19 healthy Japanese volunteers, aged 22–33 years, who were not using any medication. Electrocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…36 Evaluation can also be performed intraoperatively directly on the organ and tissue surfaces, such as the peritoneum 37 and liver. 38 Finally, its evaluation is easy to extend in pharmacological, 32 mechanical, 39 or physical 40 stress conditions. While its main application to date has been the acute setting (particularly, preshock and shock conditions 41 ), sublingual total vessel density and perfused vessel density were altered in patients with hypertension.…”
Section: Handheld Vital Microscopymentioning
confidence: 99%
“…36 Evaluation can also be performed intraoperatively directly on the organ and tissue surfaces, such as the peritoneum 37 and liver. 38 Finally, its evaluation is easy to extend in pharmacological, 32 mechanical, 39 or physical 40 stress conditions. While its main application to date has been the acute setting (particularly, preshock and shock conditions 41 ), sublingual total vessel density and perfused vessel density were altered in patients with hypertension.…”
Section: Handheld Vital Microscopymentioning
confidence: 99%
“…There are few studies evaluating acute HR modifications due to the application of dynamic WB-EMS/EMS in a single session; as in our results, they observed that the increase in HR immediately following dynamic exercise with WB-EMS was greater in both groups (obese and healthy) than with exercise alone, but the differences were not statistically significant. They concluded that WB-EMS did not alter cardiac autonomic modulation in the obese young population [ 25 , 26 ] or in the healthy [ 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies on the chronic application of dynamic WB-EMS, especially on the limb musculature and its effects on physiological parameters [ 2 , 6 , 25 , 26 , 27 , 28 , 29 , 30 ], while studies on local EMS are mostly not combined with physical exercise [ 31 ]. Few studies analyze the evolution of morphological and physiological changes during a period of training, and there may be differences depending on the type of muscles stimulated [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The device (SIXPAD; MTG Co., Ltd., Nagoya, Japan) and WB-NMES protocol have been previously described [6,10]. NMES was applied to the anterior and posterior upper arm, chest, back, abdomen, abdominal oblique, gluteus, and anterior and posterior thigh muscles.…”
Section: Study Protocolmentioning
confidence: 99%
“…Since patients with ischemic heart disease have higher blood viscosity than healthy individuals [9], increased blood viscosity due to strenuous exercise may be a risk factor for cardiovascular events. We previously reported that the single-use of WB-NMES in healthy subjects can be safely performed without any adverse effects on blood fluidity [10].…”
Section: Introductionmentioning
confidence: 99%